Recent Advances in the Development of Novel Iron–Copper Bimetallic Photo Fenton Catalysts - Bosio, Gabriela Natalia (2023)
Advanced oxidation processes (AOPs) have been postulated as viable, innovative, and efficient technologies for the removal of pollutants from water bodies. Among AOPs, photo-Fenton processes have been shown to be effective for the degradation of various types of organic compounds in industrial wastewater. Monometallic iron catalysts are limited in practical applications due to their low catalytic activity, poor stability, and recyclability. On the other hand, the development of catalysts based on copper oxides has become a current research topic due to their advantages such as strong light absorption, high mobility of charge carriers, low environmental toxicity, long-term stability, and low production cost. For these reasons, great efforts have been made to improve the practical applications of heterogeneous catalysts, and the bimetallic iron–copper materials have become a focus of research. In this context, this review focuses on the compilation of the most relevant studies on the recent progress in the application of bimetallic iron–copper materials in heterogeneous photo–Fenton-like reactions for the degradation of pollutants in wastewater. Special attention is paid to the removal efficiencies obtained and the reaction mechanisms involved in the photo–Fenton treatments with the different catalysts.